Innovative utilization of olive mill wastewater phenolics extracted by lecithin: spray-dried powders in cake formulations - Karadag, Ayse; Cakmakoglu, Selma Kayacan; Bekiroglu, Hatice; Karasu, Salih; Ozer, Hayrettin; Sagdic, Osman; Yildirim, Rusen Metin (Springer, 2024)
In the present study, the olive mill wastewater (OMW) phenolics were extracted with soy lecithin using the cloud point extraction method, and this enriched lecithin (OMW-L) was converted into spray-dried powders using maltodextrin (MD) and whey protein concentrate to be utilized as a dry food ingredient in a cake premix. The inlet temperature of 170 degrees C and a 3 mL/min feed flow rate yielded the highest powder yield (70.88 +/- 2.12%) with a moisture content of 3.78 +/- 0.03% when the mass ratio of lecithin to MD was 1:3 (w:w). The hydroxytyrosol and tyrosol contents of the powder were 42.60 +/- 4.51 mg/100 g and 15.48 +/- 2.50 mg/100 g, respectively. Vanillic acid, caffeic acid, 3-hydroxybenzoic acid, catechin, and rutin were also identified in the powders. The spray-dried OMW-L powder with a higher loading of polyphenols was then used in a cake premix, replacing 1% and 3% of wheat flour. This substitution significantly reduced the K value of the cake batter, as determined by rheological analyses. The addition of spray-dried OMW-L powder to the cake samples, particularly at higher concentrations (3%), influenced both crust and crumb color, causing changes in L*, a*, and b* values. The hardness values of the cake samples did not alter when blank or OMW-enriched lecithin powders were added; rather, the hardness value was influenced by the powder content. Overall, this research offers a different perspective on the use of OMW phenolics in food applications, especially in ready-to-use blends, and demonstrates the effects of the obtained spray-dried lecithin powders on batter rheology and cake characteristics.
Keywords: Olive mill wastewater; Hydroxytyrosol; Cloud point extraction; Lecithin powder; Cake premix